Study of patient satisfaction regarding linen and laundry services in a tertiary care hospital of north India - Sharma, Rakesh K.; Gupta, Riya; Gupta, Rajiv K.; Mahajan, Richa; Kour, Tasvinder; Chowdhary, Nahida; Chalotra, Ritika; Arif, Tasleem (International Journal Of Community Medicine And Public Health, 2022)
Background: Linen and laundry services are meant to provide clean, comfortable and hospitable services to the patients. The clean linen inculcates a sense of psychological confidence in the patients and the public and enhances their faith in the services rendered by the hospital. Objective was to study the provision of efficient linen and laundry services in a tertiary care hospital of north India. Methods: A cross-sectional study was conducted in linen and laundry services of SMGS Hospital Jammu from October 2020 to March 2021. Using convenient sampling, 300 patients or their attendants were interviewed about their satisfaction levels regarding provision of linen and laundry services. Another questionnaire was administered to the laundry plant staff to enquire about their satisfaction and motivation levels. The data was analysed and chi-square was the test of significance. Results: The findings of the study revealed an overall satisfaction rate of 91.9% among the patients/attendants regarding provision of efficient linen and laundry services. Time of recruitment and nature of job were the variables found to be significantly associated with job satisfaction among the laundry staff workers (p<0.05). Conclusions: High levels of satisfaction among the end users reflect quality of the services provided by this tertiary care hospital. Levels of motivation and job satisfaction were equally adequate among the laundry workers.